أوجه دفع العلل الطردية عند الحنفية: دراسة تأصيلية - الجهني، مسلم بن بخيت محمد الفزي (عبدالفتاح محمود إدريس, 2020)
اشتمل البحث على مقدمة وخمسة مباحث، ناقش الباحث فيها تعريف العلة وتحديد سبب الخلاف بين الأصوليين في تعريفها، وتعريف العلة الطردية من خلال تحديد مفهوم الطرد والاطراد والطردي، وتفصيل أقوال الأصوليين في الاحتجاج بالعلل الطردية، ودراسة الأوجه الأربعة لدفع العلل الطردية عند الحنفية (القول بالموجب، الممانعة، فساد الوضع، المناقضة) من خلال تعريف المصطلح وبيان وجه الدفع به عند الحنفية وذكر الفروع الفقهية للتمثيل والتطبيق، ثم خلصت لعدد من النتائج منها: 1. إن مدار الخلاف بين الحنفية والجمهور في العلل الطردية مبني على تحرير مصطلح العلة من جانب، وتحديد المفهوم الأصولي لمصطلح الطرد والاطراد من جانب أخر. 2. إن الحنفية ركزوا على قضية التأثير للوصف المعلل به في دفع العلل الطردية، فيرون أن الوصف بمجرده غير صالح لإثبات الحكم وليس بحجة بنفسه وإنما يصير حجة بواسطة التأثير، فكل وصف لم يظهر أثره يمنعون من أن يكون حجة. 3. إن إفراد الحنفية لهذه الأوجه الأربعة لدفع العلل الطردية لا يعني اختصاصها به دون غيرها، وكل ما في الأمر أن هذه الأوجه في الطردية أكثر وضوحا وظهوراً. 4. يوصي الباحث بتوجيه الباحثين بالدراسات العليا بقسم أصول الفقه إلى إعداد دراسات عميقة ومتخصصة في التأصيل النظري والتطبيقي لقوادح القياس مقارنة بين الحنفية والجمهور.
The research included an introduction and five sections, in which the researcher discussed the definition of the cause and the identification of the reason for the disagreement between the fundamentalists in defining it, the definition of the expulsive cause by defining the concept of expulsion, the exclusion and the exclusion, the details of the sayings of the fundamentalists in invoking exorbitant reasons, and the study of the four aspects of pushing the excommunicative causes of the Hanafi The objection, the corruption of the situation, the contradiction) by defining the term and explaining the way to push it to the tap and mention the jurisprudential branches for representation and application, then I concluded a number of conclusions, including: 1. The focus of the disagreement between the Hanafis and the public regarding expulsive causes is based on the liberation of the term illness on the one hand, and the definition of the fundamentalist concept of the term expulsion and expulsion. 2. The Hanafis have focused on the issue of the influence of the description explained in the payment of expulsive causes, and they see that the description by itself is not valid to prove the judgment and is not an argument by itself, but becomes an argument by means of influence. 3. The Hanafi individualization of these four aspects of expulsion of expulsion does not mean its exclusive jurisdiction over it, and all that is absent is that these aspects of expulsion are more clear and apparent. 4. The researcher recommends directing researchers in postgraduate studies in the Department of Fundamentals of Jurisprudence to prepare in-depth and specialized studies in the theoretical and practical rooting of measurement triggers for comparison between the tap and the public.
Keywords: الدين الإسلامي -- الدراسات الإسلامية -- الشريعة الإسلامية -- الفقه الإسلامي -- المذهب الحنفي